Ensuring Efficient Implementation of Lean Construction Projects Using Building Information Modeling - Svetlana S. Uvarova; Alexandr K. Orlov; Vadim S. Kankhva (Buildings, 2023)
Modern economic dynamics makes it more expedient to introduce lean construction tools into the activities of all value chain participants in construction. The need to take into account digitalization processes in construction entail an increase in the urgency of the problem related to the integration of digital technologies into the concept of lean construction. Many studies have been devoted to the problems of integrating lean construction with building information modeling (BIM) tools, which have proved their effectiveness and substantiated obstacles to their active implementation. However, issues related to assessing the cost-effectiveness of integrating lean construction with BIM and other digital technologies (if companies refuse to introduce BIM), which allow for improving the interaction of investment and construction project participants, have not been actively studied. This article examines the effectiveness of using digital tools and technologies that will contribute to the development of lean construction and reduce the corresponding losses of investment and construction projects in the example of Russia. A literature review, interviews with experts aimed at summarizing the results, as well as practical calculations taken from the existing project, were used for the purposes of this study. The main losses at each stage of an investment and construction project arising from problems in the interaction of participants in Russian construction were identified, the effects of integrating lean construction with BIM and other digital technologies were determined, an algorithm for selecting digital technologies to be integrated with lean construction was developed. The methodology for calculating the effect of the implementation of tools and principles of lean–digital interaction technologies, as well as recommendations for the implementation of tools in construction practice, were discussed.